Persepsi Mahasiswa Akuntansi terhadap Etika Akuntan Pendidik di Jurusan Akuntansi Fakultas Ekonomi Universitas Brawijaya - Meilisa, Fanita; Ludigdo, Unti (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This research has a purpose to obtain the studentsâ perception on the ethics of accounting lecturers in the Accounting Department of Brawijaya University Economic Faculty. Survey method was conducted to 125 respondents by using purposive sampling. Respondentsâ criteria are active S1 students who are in the eighth semester and have taken Business Ethics course. Descriptive analysis using frequency test was also conducted. The research shows that most students state that accounting lecturers have gained and applied eight ethics principles. It is found that 16,46% very much agrees, while 52,26% agree on the positive statements in the questionnaire. Although generally accounting lecturers have good ethics, there are still unethical behaviours, i.e. Professions Responsibility (29,23%), Public Interest (26,63%), Objectivity (10,39%), Proffessional Competence and Prudence (3,9%), Confidentiality (14,29%), Professional Behaviour (15,59%).